Pelatihan Program Urban Farming Melalui Budidaya Tanaman Sayuran Secara Hidroponik untuk Meningkatkan Keterampilan Usaha Pada Anggota Aisyiyah Cabang Karangbahagia - Diah Ayu Legowati; Edi Setiawan; Zulpahmi Zulpahmi (ASPIRASI : Publikasi Hasil Pengabdian dan Kegiatan Masyarakat, 2024)
This community service activity was carried out to members of Aisyiyah Karang Bahagia Branch. The purpose of this activity is to improve the skills of Aisyiyah members of Karang Bahagia Branch, especially in utilising the environment as a place for vegetable cultivation. This activity was carried out using two methods, namely face-to-face and online via zoom meet. This activity was carried out on 19 July 2021 to 25 July 2021. From the activities that have been carried out, the participants are very enthusiastic about the material presented by the speaker and are eager to practice farming with the hydroponic method.